On improving budget system laws for fiscal soundness - Kim, John M. (The Korea Institute of Public Finance SeoulKR, 2013)
Considers the decision-making aspect to delineate the significant influence exerted on national finance by stages of economic and fiscal development encompassing laws, political systems and administrative levels.